Intravenous immunoglobulin therapy: usage patterns and response to treatment in Qatar over ten years - Taha, Salma A.; Thalappil, Sherin; Ali, Ramzy M.; Fatima, Haajra; Imameldin, Asaad Omer A.; Aqel, Sami; Abdelaal, Ahmed M.; Siepmann, Timo; Barlinn, Jessica; Al-Nesf, Maryam A. (Frontiers in Immunology, 2024)
BackgroundIVIg is a blood-derived antibody product initially designed as a replacement therapy in inborn errors of immunity (IEIs). However, over the last 50 years, IVIg has been used to treat a growing range of autoimmune, autoinflammatory, and secondary immunodeficiency disorders. The US FDA has licensed IVIg for use in the treatment of nine clinical indications; although, IVIg global usage extends to off-label indications with variable treatment responses. Data from Qatar on the use of IVIg is scarce; thus, hampering the formulation of local policies. This study aimed to examine the utilization patterns, clinical indications, and safety profile of IVIg usage in Qatar; a nation with a predominantly young population, and to investigate the response rates to short- and long-term IVIg treatment, as well as explore associations between age at first IVIg dose, clinical indication, and treatment response.MethodsA retrospective chart review was conducted of patients who received IVIg between March 2009, and March 2019, in Hamad General Hospital, Qatar. Demographics, immediate adverse effects of IVIg, and treatment response were collected. IVIg clinical indications were categorized into FDA- and/or EMA-approved, those supported by international guidelines; those approved as second-line therapy, and those with low or no supportive evidence.ResultsIVIg was used for 63 indications during the 10-years. The age of patients skewed towards a younger demographic (median (IQR) 24 (44-6) years); however, no significant differences in response to short- and long-term treatment between age groups were observed. Of the 841 patients, 62% received IVIg in concordance with international recommendations, while 14% bestowed the treatment for indications with low or no supportive evidence. Immediate IVIg adverse effects were documented in 4% of patients in all of the infusions received, with headaches being the most prevalent (1.8%). Variable treatment responses were observed, with the highest recovery reported in immune thrombocytopenic purpura (35%), followed by transverse myelitis (28%).ConclusionThis study provided crucial insights into IVIg utilization, safety, and treatment outcomes in Qatar’s young population. Despite variability in treatment responses and off-label use, adherence to international recommendations remained eminent. Further research is warranted to inform local guidelines and optimize IVIg therapy outcomes.